Children with Chest Pain Visiting the Emergency Department - Chien-Heng Lin; Wei-Ching Lin; Yung-Jen Ho; Jeng-Sheng Chang (Elsevier, 2008)
Chest pain is a common complaint in children visiting the emergency department (ED). True organic problems like cardiac disease are rare. We assess and analyze the etiology of chest pain among children visiting a pediatric ED in one medical center. Methods: We retrospectively reviewed the medical records of children with chest pain who visited our ED between September 2002 and June 2005. Any case of trauma-associated chest pain was excluded from this study. Results: A total of 103 patients (64 boys, 39 girls; mean age, 13 years; age range, 4-17 years) were enrolled into this study; 101 patients had chest radiograms (98.1%). Pneumonia was identified in five patients and pneumothorax in three. Eighty-seven patients had electrocardiogram study (84.5%) and four of them showed abnormalities. Additional diagnostic tests were performed in 64 patients (62.1%), including complete blood count analysis and echocardiography. Echocardiograms were performed in 15 (14.6%) patients. Six of them showed minor abnormality. Panendoscopy was done in six (5.8%) patients, and gastroesophageal reflux was found in three. Eleven (10.7%) patients were admitted to hospital because of pneumonia, pneumothorax or arrhythmia. Overall, idiopathic chest pain was the most common diagnosis (59.2%). Other associated disorders were pulmonary (24.3%), musculoskeletal (6.7%), gastrointestinal (5.8%), cardiac (2.0%) and miscellaneous (2.0%). Conclusion: The most common cause of chest pain prompting a child to visit the ED is idiopathic chest pain. Careful physical examination can reveal important clues and save much unnecessary examinations.